DEVELOPING TEACHING STUDENTS’ WRITTEN SPEECH - Aygun Elxan Mehdiyeva (Foundations and Trends in Research, 2026)
When teaching English to students in non-linguistic groups, it is necessary to define the role and place of writing and written speech in the practical English language course for international students. Teaching students’ written speech will be more effective and efficient if it is based on the following principles: teaching international students’ written speech is based on a communicative-activity-based approach and is focused on the students’ educational and communicative needs and the professional written and spoken skills required by English language teachers in their teaching [1.98]. The problem of teaching written speech is considered an integral part of the overall professional training of English language teachers.